2010
DOI: 10.1074/jbc.m109.036814
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Type of E3 Ligase for the Ufm1 Conjugation System

Abstract: The ubiquitin fold modifier 1 (Ufm1) is the most recently discovered ubiquitin-like modifier whose conjugation (ufmylation) system is conserved in multicellular organisms. Ufm1 is known to covalently attach with cellular protein(s) via a specific E1-activating enzyme (Uba5) and an E2-conjugating enzyme (Ufc1), but its E3-ligating enzyme(s) as well as the target protein(s) remain unknown. Herein, we report both a novel E3 ligase for Ufm1, designated Ufl1, and an Ufm1-specific substrate ligated by Ufl1, C20orf11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
306
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(323 citation statements)
references
References 32 publications
(37 reference statements)
16
306
1
Order By: Relevance
“…The role of UFBP1 (UFM1-binding protein 1 containing a PCI domain, also known as C20orf116 and DDRGK1) modification by UFM1 is less clear. However, it localizes to the endoplasmic reticulum (ER) and is involved in ER stress response (4,7,8). Interestingly, conditions that induce ER stress lead to increased expression of components of the UFM1 conjugation system, whereas their downregulation exacerbates ER stress and sensitizes cells to apoptosis (5)(6)(7)(8)(9).…”
Section: Ufm1mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of UFBP1 (UFM1-binding protein 1 containing a PCI domain, also known as C20orf116 and DDRGK1) modification by UFM1 is less clear. However, it localizes to the endoplasmic reticulum (ER) and is involved in ER stress response (4,7,8). Interestingly, conditions that induce ER stress lead to increased expression of components of the UFM1 conjugation system, whereas their downregulation exacerbates ER stress and sensitizes cells to apoptosis (5)(6)(7)(8)(9).…”
Section: Ufm1mentioning
confidence: 99%
“…To exclude any role for additional cellular proteins in this process, we made use of a previously published in vitro thioester formation assay (4) in which the production of thioester intermediates (UBA5-UFM1 and UFC1-UFM1, respectively) reflects the activity of UBA5 as a UFM1-activating (E1) enzyme. In the first reaction, involving purified UBA5 and UFM1, we observed that removal of either the LIR/UFIM or the whole C terminus resulted in reduced amounts of the UBA5-UFM1 intermediate.…”
Section: Uba5 Interacts With Ufm1 and Lc3/gabarap Proteins Via An Evomentioning
confidence: 99%
“…Solution structure studies have shown that Ufm1 adopts a similar ␤-grasp fold as seen in all other Ubls (12). Other studies have uncovered additional components in the Ufm1 conjugation or ufmylation pathway (13)(14)(15)(16)(17). Ufm1 is activated by an E1 enzyme identified as Uba5 and then is transferred to a conjugating enzyme (E2) Ufc1 (16,18).…”
mentioning
confidence: 99%
“…Such mediators may include p35 [26] and other potential C53/LZAP-interacting protein such as Disrupted-in-Schizophrenia 1 (DISC1) protein, which is also known to bind the microtubule [27,28]. Meanwhile, a relatively large fraction of cytoplasmic C53/LZAP is associated with light membranes, such as the ER (Figure 6B and [12]), probably through its interaction with the ER protein RCAD (also known as Ufl1, NLBP and MAXER) [12,[15][16][17]. Therefore, C53/LZAP appears to serve as an important linker between the microtubule network and the endomembrane system.…”
Section: Discussionmentioning
confidence: 99%
“…In correlation with its potential diverse functions, C53/LZAP was found in multi-subcellular compartments, including cytosol, nucleus, nucleolus and centrosomes [5,7,12,13]. Not surprisingly, it was reported to interact with a wide range of proteins, including p35 [3], Rel A [5], Chk1/2 [7], PAK4 [9], ARF [4], p38 MAPK [14], Ufl1 (also known as RCAD, NLBP and Maxer) [12,[15][16][17] and γ-tubulin [13]. Yet the underlying biochemical nature of these protein-protein interactions remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%